Changes in adipose glucocorticoid metabolism before and after bariatric surgery assessed by direct hormone measurements. (13th June 2013) - Methlie, Paal; Dankel, Simon; Myhra, Tone; Christensen, Bjørn; Gjerde, Jennifer; Fadnes, Dag; Våge, Villy; Løvås, Kristian; Mellgren, Gunnar
<x xml:space="preserve">Abstract</x> Objectives Increased intra‐adipose cortisol is thought to promote obesity, but few human studies have investigated intra‐adipose glucocorticoid hormones and none have demonstrated prospective changes with fat loss. Design and Methods Subcutaneous adipose tissue (SAT) was obtained from obese subjects before and 1‐year after surgery‐induced fat loss, and from nonobese controls. In a second similar cohort of obese subjects, adipocytes and stromal‐vascular fraction were isolated. Intra‐adipose cortisol and cortisone levels were analyzed by liquid chromatography mass spectrometry and HSD11B1/HSD11B2 mRNA by qPCR. Results SAT cortisol/cortisone ratio before fat loss, median 4.8 (interquartile range, 4.1‐5.7), was higher than after fat loss, 1.9 (1.0‐2.7) (P = 0.001), and compared to nonobese controls, 3.2 (2.4‐3.9) (P = 0.005). Cortisone before fat loss, 2.3 (1.2‐2.9) nmol/kg, was lower than after fat loss, 5.8 (3.0‐10.2) nmol/kg (P = 0.042), and compared to controls, 5.1 (3.8‐6.7) nmol/kg (P = 0.013). HSD11B1 was predominantly expressed in mature adipocytes, whereas HSD11B2 was expressed at a higher level in stromal‐vascular fraction. Conclusions The intra‐adipose glucocorticoid metabolism was markedly altered in the extremely obese state with increased cortisol levels relative to cortisone, whereas fat loss restored this balance approximating nonobese subjects. Changes were more pronounced for cortisone than cortisol, suggesting an adaptive response to insufficient intra‐adipose cortisol levels in obesity.